Battery

By using silicon-based fluorophosphate and cyclic sulfate as electrolyte additives in lithium-ion batteries, a stable interface film is constructed, and the circulation and thermal stability problems of lithium-ion batteries under high voltage and/or high nickel conditions are solved, and low impedance, long cycle and high/low temperature resistance are achieved.

CN119695238AActive Publication Date: 2025-03-25JIUJIANG TINCI ADVANCED MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411742304.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-25
Estimated Expiration
2044-11-29

Smart Images

  • Figure CN119695238A_ABST
    Figure CN119695238A_ABST
Patent Text Reader

Abstract

The invention provides a battery, which comprises a positive plate, a negative plate, a diaphragm and an electrolyte, the positive plate comprises a current collector and a positive coating arranged on at least one functional surface of the current collector, the positive coating comprises a positive active material, the chemical composition of the positive active material comprises LiNixCoyMzO2, M is Mn and / or Al, x + y + z = 1, ytt, and y + z = 1, ytt; 0.3 part; the electrolyte comprises a first additive and a second additive. By introducing the first additive and the second additive, the battery disclosed by the invention can show excellent performances of low impedance, long circulation and high / low temperature resistance under high voltage and high nickel conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a battery. Background Art

[0002] In order to meet market demand and promote the further development of the lithium battery industry, the development of ternary positive electrode materials with higher energy density has become the goal pursued by many industry personnel. At present, improving the energy density of the positive electrode can be achieved by reducing the cobalt content, because reducing the cobalt content brings two results. One is to increase the charging cut-off voltage of the battery. Taking the 5 series ternary as an example, when the charging cut-off voltage is increased from 4.2V to 4.3V, the discharge capacity of the positive electrode material is significantly improved. The second is to increase the nickel content in the system, which also significantly improves the discharge capacity of the positive electrode material.

[0003] However, in practical applications, high voltage or high nickel content also brings great challenges to the comprehensive performance of lithium batteries. Among them, increasing the charging voltage will lead to the deterioration of the material's cycle stability, which is specifically reflected in: the dissolution of transition metals such as nickel, cobalt and manganese and their deposition on the negative electrode surface, the oxidation and decomposition of the electrolyte, and the large-scale gas production of the battery. Increasing the nickel content will affect the thermal stability of the material, which is specifically reflected in: when the battery faces high temperatures (greater than or equal to 40°C), the residual LiOH and highly active Ni-O on the surface of the material will react with the electrolyte, and the released O2 will react with the electrolyte components to produce thermal runaway. Summary of the invention

[0004] The present invention provides a battery, which can effectively improve the cycle and storage stability of lithium-ion batteries under high voltage and / or high nickel conditions. Specifically, the battery can solve at least one of the problems caused by high voltage, including the dissolution of transition metals such as nickel, cobalt and manganese and their deposition on the negative electrode surface, oxidative decomposition of the electrolyte, and large-scale gas production of the battery. It can also solve at least one of the problems caused by high nickel, including the residual LiOH and highly active Ni-O on the surface of the material reacting with the electrolyte at a high temperature (greater than or equal to 40°C), and the released O2 reacting with electrolyte components to produce thermal runaway.

[0005] In detail, the present invention provides a battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet includes a current collector and a positive electrode coating disposed on at least one functional surface of the current collector, wherein the positive electrode coating includes a positive electrode active material, and the chemical composition of the positive electrode active material includes: LiNi x Co y M z O2, wherein M is Mn and / or Al, x+y+z=1, y<0.3; the electrolyte comprises: a first additive and a second additive, the first additive containing at least one of the silicon-based fluorophosphate compounds shown in Formula 1-1 to Formula 1-4:

[0006]

[0007] The second additive includes at least one of cyclic sulfate esters, cyclic sulfites and cyclic sulfonate ester compounds.

[0008] Further, x≥0.8.

[0009] Furthermore, 0.5≤x≤0.7, and / or the charging cut-off voltage of the battery is ≥4.3V.

[0010] Furthermore, the chemical composition of the positive electrode active material includes: LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.83 Co 0.11 Mn 0.06 O2、LiNi 0.92 Co 0.05 Mn 0.03 O2、LiNi 0.8 Co 0.1 Al 0.1 At least one of O2.

[0011] Furthermore, the chemical composition of the positive electrode active material includes: LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.55 Co 0.15 Mn 0.30 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.65 Co 0.07 Mn 0.28 O2、LiNi 0.6 Co 0.1 Mn 0.3 O2、LiNi 0.55 Co 0.15 Mn 0.30 O2.

[0012] Further, the cyclic sulfate ester compound includes at least one of vinyl sulfate, propylene sulfate, vinylidene sulfate, catechol sulfate, bis-spiropropylene sulfate, bis-vinyl sulfate, 4,5-bis(4-vinyl sulfate)ethylene carbonate, and methylene methane disulfonate;

[0013] The cyclic sulfite compounds include ethylene sulfite and / or propylene sulfite;

[0014] The cyclic sulfonate compound includes at least one of 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, 2,4-butane sultone, 3-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 1-fluoro-1,3-propane sultone, and ethylene sulfonic acid difluoro lithium phosphate triethylamine salt.

[0015] Furthermore, in the electrolyte, the mass percentage of the first additive is 0.05wt%-5.0wt%;

[0016] And / or, in the electrolyte, the mass percentage of the second additive is 0.1wt%-4.0wt%.

[0017] Furthermore, in the electrolyte, the mass percentage of the first additive is 0.5wt%-2.5wt%;

[0018] And / or, in the electrolyte, the mass percentage of the second additive is 0.5-3wt%.

[0019] Furthermore, in the electrolyte, the mass ratio of the first additive to the second additive is 1:0.1-4.

[0020] Furthermore, lithium salts and non-aqueous organic solvents are also included.

[0021] Furthermore, in the electrolyte, the mass percentage of lithium salt is 6wt%-25wt%.

[0022] The battery provided by the present invention can exhibit low impedance, long cycle, and high / low temperature resistance under high voltage and / or high nickel conditions by adding a first additive and a second additive to a non-aqueous electrolyte. Specifically, the first additive, a silicon-based fluorophosphate compound, has a lower redox potential, reacts preferentially to the solvent and inhibits the decomposition of the solvent. When the first additive and the second additive are both applied to a high nickel system, on the one hand, the first additive can be preferentially oxidized to polysiloxane to construct an organic interface film, thereby preventing the oxygen released from the electrode material from oxidizing the electrolyte components. The first additive is rich in Si-O structure and has a good affinity for the transition metal of the positive electrode, especially for high-content Ni components, and has a good stabilizing effect on the Ni metal in the positive electrode material, which can inhibit Li+ / Ni 2+Mixed arrangement, further, the CEI film of polysiloxane has high mechanical strength, and can inhibit the grain boundary cracking caused by the volume change of the high-nickel positive electrode during the charge and discharge process. On the other hand, the interface film rich in inorganic sulfate, sulfite, alkyl lithium sulfonate, alkyl lithium sulfate, and lithium sulfide components constructed by the combination with the second additive improves the stability of the interface film while maintaining a low interface impedance, thereby improving the high temperature stability and cycle stability of the high-nickel system battery as a whole; when the first additive and the second additive are simultaneously applied to the high-voltage system, the first additive silicon-based fluorophosphate compound not only shows the construction of an interface film with good stability, but also shows a good binding and consumption effect on the free radical ions generated by the second additive, avoiding its consumption and decomposition of solvents and lithium salts, especially in inhibiting the abnormal acidity caused by decomposition by-products, showing excellent effects, wherein the silicon-based structure can bind to the acidic components in the electrolyte and further participate in polymerization, converting free acidic substances into beneficial interface film components, effectively alleviating the problems of high-temperature gas production, capacity attenuation and cycle diving of the battery caused by increased acidity of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0024] Figure 1 The graph is a capacity retention rate diagram of lithium ion batteries containing the electrolytes of Examples 1, 2 and Comparative Example 1 at room temperature cycles;

[0025] Figure 2 A graph showing the capacity retention rate of lithium-ion batteries containing the electrolytes of Examples 1, 2 and Comparative Example 1 at high temperature cycles;

[0026] Figure 3 A graph showing the battery thickness and impedance change rate of lithium-ion batteries containing the electrolytes of Examples 1, 2 and Comparative Example 1 after high-temperature storage;

[0027] Figure 4 The figure is a graph showing the change in discharge capacity retention rate of lithium-ion batteries containing the electrolytes of Examples 1, 2 and Comparative Example 1 at low temperatures. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0029] In one aspect, the present invention provides a battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a current collector and a positive electrode coating disposed on at least one functional surface of the current collector, wherein the positive electrode coating comprises a positive electrode active material, and the chemical composition of the positive electrode active material comprises: LiNi x Co y M z O2, wherein M is Mn and / or Al, x+y+z=1, y<0.3; the electrolyte comprises: a first additive and a second additive, the first additive containing at least one of the silicon-based fluorophosphate compounds shown in Formula 1-1 to Formula 1-4:

[0030]

[0031] The second additive includes at least one of cyclic sulfate esters, cyclic sulfites and cyclic sulfonate ester compounds.

[0032] For conventional ternary lithium-ion batteries, the introduction of sulfate compounds (such as vinyl sulfate (DTD) and / or sulfonate compounds (PS) has good film-forming properties. During the first charge and discharge process, free radical structures can be generated to combine with solvents and lithium ions to form inorganic sulfates, sulfites, alkyl lithium sulfonates, alkyl lithium sulfates, lithium sulfides, etc., which can build SEI / CEI interface films and avoid HF and F in the electrolyte. - Components such as sulfonates and sulphonates corrode the positive electrode active material, thereby improving the cycle stability and high temperature storage performance of the battery. However, in batteries under high nickel systems or high voltage medium nickel systems, the interfacial film constructed by sulfate ester compounds and / or sulfonate ester compounds has limited protection effect on the electrode / electrolyte. For high nickel systems, the thermal stability of the electrode material is reduced, and the residual LiOH and highly active Ni -The side reactions of O and electrolyte are intensified, and the released O2 reacts with electrolyte components to produce thermal runaway, which will consume a lot of film-forming processes of sulfate compounds and / or sulfonate compounds, and cannot maintain the protection or repair effect on SEI / CEI membranes. This leads to serious damage to the interface film in the later stage of cycling / storage, intensified electrolyte oxidation and redundant accumulation of by-products. For high-voltage systems, the increase in voltage at the electrode interface will cause sulfate compounds and / or sulfonate compounds to produce more free radical ions, which will excessively consume solvents and lithium salts, reduce the initial capacity, and increase the thickness of the interface film, resulting in increased interface impedance. Especially in long-term cycling / storage, the by-products produced by the decomposition of sulfate compounds and / or sulfonate compounds at high voltage will increase the acidity of the electrolyte, accelerate the corrosion of electrolyte components, electrode / electrolyte interfaces, and electrode active materials, which is not only not conducive to solving the problems of poor stability of electrode active materials, dissolution of transition metals such as nickel, cobalt, and manganese and deposition on the negative electrode surface, oxidation and decomposition of electrolytes, and large-scale gas production of batteries, but will also cause battery capacity to drop and safety hazards. Therefore, in order to avoid the problems of sulfate compounds and / or sulfonate compounds in high-nickel systems or high-voltage medium-nickel systems, the present invention can well solve this series of problems by introducing a first additive and a second additive, wherein the first additive, a silicon-based fluorophosphate compound, has a lower redox potential, reacts preferentially to the solvent and inhibits the decomposition of the solvent. When the first additive and the second additive are applied to the high-nickel system, the first additive can be preferentially oxidized to polysiloxane to construct an organic interface film, thereby preventing the oxygen released in the electrode material from oxidizing the electrolyte components. The Si-O-rich structure has a good affinity for the transition metal of the positive electrode, especially for the high-content Ni component, and has a good stabilizing effect on the Ni metal in the positive electrode material, which can inhibit the Li+ / Ni 2+Mixed, further, the CEI film of polysiloxane has high mechanical strength, and can inhibit the grain boundary cracking caused by the volume change of the high nickel positive electrode during the charge and discharge process. The interface film rich in inorganic sulfate, sulfite, alkyl sulfonate lithium, alkyl sulfate lithium, and lithium sulfide components constructed by the second additive improves the stability of the interface film while maintaining a low interface impedance, and overall improves the high temperature stability and cycle stability of the high nickel system battery. When the first additive and the second additive are applied to the high voltage system at the same time, in addition to showing the construction of an interface film with good stability, the first additive also shows a good binding and consumption effect on the free radical ions generated by the second additive, avoiding its consumption and decomposition of solvents and lithium salts, especially in inhibiting the abnormal acidity caused by decomposition byproducts, showing excellent effects, wherein the silicon-based structure can bind to the acidic components in the electrolyte and further participate in polymerization, converting free acidic substances into beneficial interface film components, effectively alleviating the problems of high temperature gas production, capacity attenuation and cycle diving of the battery caused by increased electrolyte acidity. In addition, when the first additive includes the structure shown in Formula 1-3 and / or Formula 1-2, its solubility in the electrolyte can also be reduced. When the first additive includes the structure shown in Formula 1-1, the introduction of unsaturated olefin groups at the end groups can further construct a protective layer with a cross-linked network structure, thereby increasing the adhesion of the CEI film on the positive electrode side. When the first additive includes the structure shown in Formula 1-4, the introduction of phenyl structures at the end groups can also enhance the deformation resistance of the interface film, thereby further enhancing the mechanical strength of the CEI film.

[0033] Taking the above reasons into consideration, the battery of the present invention can exhibit excellent performances of low impedance, long cycle, and high / low temperature resistance under high voltage and / or high nickelization conditions.

[0034] In a specific embodiment, x≥0.8. In the above embodiment, by further increasing the nickel content in the positive electrode system, the energy density of the battery can be further increased.

[0035] In a specific embodiment, 0.5≤x≤0.7, and / or the battery has a charge cut-off voltage ≥4.3 V. In the above embodiment, by further limiting the nickel content and / or the battery charge cut-off voltage, the battery capacity and output power can be further improved.

[0036] In one embodiment, the chemical composition of the positive electrode active material includes: LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.83 Co 0.11 Mn 0.06 O2、LiNi 0.92 Co 0.05 Mn 0.03O2、LiNi 0.8 Co 0.1 Al 0.1 At least one of O2.

[0037] In one embodiment, the chemical composition of the positive electrode active material includes: LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.55 Co 0.15 Mn 0.30 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.65 Co 0.07 Mn 0.28 O2、LiNi 0.6 Co 0.1 Mn 0.3 O2、LiNi 0.55 Co 0.15 Mn 0.30 O2.

[0038] As for the negative electrode sheet of the battery, the present invention does not make any special limitation. In some embodiments, the negative electrode sheet includes a current collector and a negative electrode coating arranged on at least one functional surface of the current collector, and the negative electrode coating includes a negative electrode active material. The negative electrode material can be a conventional material in the art, including but not limited to one or more of carbonaceous materials, silicon-carbon materials, alloy materials, and lithium-containing metal composite oxides. Furthermore, the negative electrode material is one or more of graphite, soft carbon, hard carbon, silicon, silicon-oxygen compounds, silicon-carbon composites, and lithium titanate.

[0039] In some embodiments, the positive electrode coating and the negative electrode coating further include: a conductive agent, a binder, and optionally a dispersant. The conductive agent of the positive electrode coating is at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the conductive agent of the negative electrode coating is different from the negative electrode active material and can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binders of the positive electrode coating and the negative electrode coating are each independently at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the dispersants of the positive electrode coating and the negative electrode coating are each independently at least one of sodium carboxymethyl cellulose, triethylhexyl phosphoric acid, and sodium dodecyl sulfate.

[0040] The thickness, surface density, thickness of the negative electrode coating, and thickness of the positive electrode coating of the positive electrode sheet and the negative electrode sheet are not specifically limited in the present invention. In a specific embodiment, the thickness of the positive electrode sheet or the negative electrode sheet is 40-120 μm, and the surface density is 3-10 mg / cm 2 , the thickness of the negative electrode coating or the thickness of the positive electrode coating is 20-60 μm. In some embodiments, the negative electrode coating comprises, by mass percentage, 94%-97% of negative electrode active material, 1%-2.5% of conductive agent, 1.2%-2.5% of binder and 0.5%-1.5% of dispersant.

[0041] In some embodiments, the positive electrode coating comprises, by mass percentage, 94%-97% of positive electrode active material, 1%-2.5% of conductive agent, 1.2%-2.5% of binder and 0.5%-1.5% of dispersant.

[0042] The technicians can select conventional diaphragms for the above-mentioned diaphragms, such as polyolefins, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, etc.

[0043] In a specific embodiment, the cyclic sulfate ester compound includes at least one of vinyl sulfate (DTD), propylene sulfate, vinylidene sulfate, catechol sulfate, dispiropropylene sulfate, divinyl sulfate, 4,5-bis(4-vinyl sulfate)ethylene carbonate, and methylene methane disulfonate (MMDS);

[0044] The cyclic sulfite compounds include ethylene sulfite and / or propylene sulfite;

[0045] The cyclic sulfonate compound includes at least one of 1,3-propane sultone (PS), 1,3-propylene sultone (PES), 1,4-butane sultone, 2,4-butane sultone, 3-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 1-fluoro-1,3-propane sultone, and triethylamine lithium difluorophosphate of ethylene sulfonic acid.

[0046] In a specific embodiment, in the electrolyte, the mass percentage of the first additive is 0.05wt%-5.0wt%;

[0047] And / or, in the electrolyte, the mass percentage of the second additive is 0.1wt%-4.0wt%.

[0048] Among them, the first additive within the above mass percentage range has a significant effect on reducing battery impedance, improving low-temperature discharge and cycle performance. If the mass percentage of the first additive is higher than 5.0wt%, it will lead to excessive production of disiloxane and fluorosilane components, which will have a negative effect on battery impedance, gas production and capacity retention. If it is lower than 0.05wt%, the silane structure is less, and Li3PO3, Li x PO y F z The lithium salt film-forming components are relatively few and cannot effectively coat the positive / negative electrode materials, so the effect of improving battery performance is limited.

[0049] The second additive within the above mass percentage range can achieve a good balance between the amount of solvent consumed and the construction of SEI / CEI interface films rich in inorganic sulfates, sulfites, alkyl lithium sulfonates, alkyl lithium sulfates, lithium sulfides, etc. If the content of the second additive is too low, although the consumption of the electrolyte is greatly reduced, the inorganic sulfur-containing lithium salt in the constructed interface film is relatively small, and it is impossible to further reduce the impedance and improve the circulation and storage stability under high temperature conditions. If the content of the second additive is too high, it will not only lead to excessive consumption of the electrolyte, but also gas production in the battery. The thickness of the constructed SEI / CEI interface film will increase, resulting in an increase in battery impedance and poor circulation and storage performance.

[0050] In a more preferred embodiment, in the electrolyte, the mass percentage of the first additive is 0.5wt%-2.5wt%;

[0051] And / or, in the electrolyte, the mass percentage of the second additive is 0.5-3wt%.

[0052] In a specific embodiment, in the electrolyte, the mass ratio of the first additive to the second additive is 1:0.1-4.

[0053] Among them, the silicon-based structure produced by silicon-based fluorophosphate compounds has a certain quenching effect on the alkyl radicals after the ring-opening reaction, blocking the reaction of alkyl radicals with solvent molecules to cause serious gas production and impedance increase problems. The above-mentioned implementation method can better exert the synergistic effect of the two additives by controlling the ratio of the two additives, constructing a low-impedance interface film with uniform thickness, dense structure, corrosion resistance, and high-temperature stability, hindering HF corrosion of electrolyte and electrodes, reducing battery impedance, inhibiting battery gas expansion, and improving low-temperature performance, so as to optimize the cycle and storage performance of the battery under different temperature conditions.

[0054] In one specific embodiment, a lithium salt and a non-aqueous organic solvent are also included.

[0055] The present invention does not specifically limit the above-mentioned lithium salt, and the technician can select conventional lithium salt materials. Exemplarily, the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium perfluorobutylsulfonate and fluorinated fatty acid lithium.

[0056] The present invention does not specifically limit the above-mentioned non-aqueous organic solvent. The technician can select a conventional non-aqueous organic solvent. For example, the non-aqueous organic solvent includes cyclic carbonates such as ethylene carbonate (EC) and propylene carbonate (PC), linear carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC), and at least one of carboxylic acid esters such as ethyl acetate (EA), propyl acetate (PA), ethyl propionate (EP), and propyl propionate (PP).

[0057] In a specific embodiment, in the electrolyte, the mass percentage of lithium salt is 6wt%-25wt%.

[0058] Among them, when the lithium salt is within the above range, the lithium salt can be dissolved in the organic solvent to form an electrolyte with high stability and good lithium conductivity. At the same time, the viscosity of the electrolyte can be appropriate, so that lithium ions can migrate quickly in the electrolyte, thereby making the battery exhibit excellent cycle performance.

[0059] In a more preferred embodiment, the mass percentage of the lithium salt is 10wt%-15wt%.

[0060] Illustratively, the mass percentage of the non-aqueous organic solvent is 60 wt %-92 wt %, preferably 65 wt %-85 wt %.

[0061] Among them, when the organic solvent is within the above range, the lithium salt can be fully dissolved in the electrolyte, which is helpful to prepare an electrolyte with high conductivity and strong stability, so that the electrochemical performance of the battery is stable.

[0062] The present invention is further described below in conjunction with specific embodiments:

[0063] Among them, the CAS number of the silicon-based fluorophosphate compound represented by the following formula 1-1 is: 2708941-25-5;

[0064] The CAS number of the silicon-based fluorophosphate compound represented by the following formula 1-2 is: 4414-25-9;

[0065] The CAS number of the silicon-based fluorophosphate compound represented by the following formula 1-3 is: 4414-26-0;

[0066] The CAS number of the silicon-based fluorophosphate compound shown in the following formula 1-4 is: 6231-57-8.

[0067] Example 1

[0068] This example provides a battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet includes an aluminum foil and a positive electrode material layer arranged on the front and back sides of the aluminum foil. The positive electrode active material of the positive electrode material layer is LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), electrolyte, calculated by mass fraction, includes 12.5% ​​LiPF6, 1.0% first additive, 1.5% second additive, and the balance is non-aqueous organic solvent, wherein the first additive is a silicon-based fluorophosphate compound shown in formula Ι-2, the second additive is vinyl sulfate (DTD), and the non-aqueous organic solvent is composed of vinyl carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a mass ratio of 3:5:2.

[0069] The preparation method comprises the following steps:

[0070] 1. Positive electrode preparation: LiNi 0.5 Co 0.2 Mn 0.3 The O2 positive electrode active material, conductive agent SuperP (conductive carbon black), conductive agent CNT (carbon nanotube), and adhesive PVDF (polyvinylidene fluoride) were mixed evenly in a mass ratio of 96.3:2:0.5:1.2, and vacuum stirred until the fluidity was uniform. Then, the slurry was evenly coated (coating thickness was 50 μm) on the front and back of the aluminum foil, and then dried at 85°C, cold pressed, trimmed, cut, stripped, and vacuum dried at 85°C for 12 hours. After welding the pole ears, the surface density was 33 mg / cm 2 The positive electrode.

[0071] 2. Negative electrode preparation: Graphite negative electrode active material, conductive agent Super P (conductive carbon black), thickener CMC (sodium carboxymethyl cellulose), and adhesive SBR (styrene-butadiene rubber latex) were fully mixed into a uniform slurry at a mass ratio of 96:1.5:1.5:2. After coating on both sides of the copper foil (coating thickness of 60 μm), it was dried at 85°C, and then cold pressed, trimmed, cut into pieces, and striped. Finally, it was dried under vacuum conditions at 85°C for 12 hours, and the electrode ears were welded to obtain a surface density of 19.3 mg / cm 2 The negative electrode.

[0072] 3. Diaphragm: A 9 μm thick polyethylene porous polymer film is used as the substrate, and a 2 μm adhesive coating is coated on both sides of the substrate.

[0073] 4. Battery preparation

[0074] The above-mentioned positive electrode sheet, separator and negative electrode sheet are stacked in sequence and then wound into a bare cell with a theoretical capacity of 1600mAh (the actual capacity will be less than the theoretical capacity). The bare cell is placed in an outer packaging aluminum foil and vacuum-baked at 75°C for 10 hours. Different electrolytes can be injected into the cells respectively. After vacuum packaging, standing, formation, aging, capacity division and other processes, the lithium-ion battery is completed.

[0075] Example 2-30

[0076] The method is basically the same as Example 1, except that the conditions shown in Table 1 are changed.

[0077] Embodiment 31

[0078] This example provides a lithium-ion battery, including the electrolyte of the above-mentioned embodiment 1. The preparation and assembly process of each part of the lithium-ion battery is basically the same as that of embodiment 1, except that: the positive electrode material is LiNi 0.6 Co 0.2 Mn 0.2 O2.

[0079] Embodiment 32

[0080] This example provides a lithium-ion battery, including the electrolyte of the above-mentioned embodiment 1. The preparation and assembly process of each part of the lithium-ion battery is basically the same as that of embodiment 1, except that: the positive electrode material is LiNi 0.8 Co 0.1 Al 0.1 O2.

[0081] Embodiment 33

[0082] This example provides a lithium-ion battery, including the electrolyte of the above-mentioned embodiment 1. The preparation and assembly process of each part of the lithium-ion battery is basically the same as that of embodiment 1, except that: the positive electrode material is LiNi 0.92 Co 0.05 Mn 0.03 O2.

[0083] Comparative Example 1

[0084] The method is basically the same as that of Example 1, except that the first additive is not added to the electrolyte.

[0085] Comparative Example 2

[0086] The method is basically the same as that of Example 1, except that no second additive is added to the electrolyte.

[0087] Comparative Example 3

[0088] The method is basically the same as Example 1, except that the structure of the first additive in the electrolyte is as shown in Formula II:

[0089]

[0090] Comparative Example 4

[0091] This example provides a lithium-ion battery, including the electrolyte of Example 1. The preparation and assembly process of each part of the lithium-ion battery is basically the same as that of Experimental Example 1, except that the positive electrode material is LiNi 0.6 Co 0.3 Mn 0.1 O2.

[0092] Comparative Example 5

[0093] This example provides a lithium ion battery, which is basically the same as Example 1, except that the structure of the first additive in the electrolyte is as shown in Formula Ш:

[0094]

[0095] Table 1

[0096]

[0097]

[0098] Performance Test:

[0099] 1. The above lithium-ion batteries were subjected to impedance, cycle and high and low temperature performance tests. The test methods are as follows. The test results are shown in Table 2:

[0100] 1.1, 25 ℃ room temperature cycle test: at 25 ℃, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, and then discharge to 2.75V at 1.0C constant current. Repeat the charge and discharge steps for 1000 cycles. The discharge capacity of the 1000th cycle and the first cycle are recorded and the capacity retention rate is obtained by dividing the two. The room temperature cycle capacity retention rate curves of Examples 1, 2 and Comparative Example 1 are shown in Figure 1 .

[0101] 1.2, 45 ℃ high temperature cycle test: at 45 ℃, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, and then discharge to 2.75V at 1.0C constant current. Repeat the charge and discharge steps for 800 cycles. The discharge capacity of the 800th cycle and the first cycle are recorded and the capacity retention rate is obtained by dividing the two. The high temperature cycle capacity retention rate curves of Examples 1, 2 and Comparative Example 1 are shown in Figure 2 .

[0102] 1.3, 60℃ high temperature 30-day storage test: At 25℃, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, then discharge to 2.75V at 1.0C constant current, the discharge capacity is recorded as C1. At 25℃, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, then transfer the battery to 60℃ for 30 days, then discharge to 2.75V at 1.0C constant current, the discharge capacity is recorded as C2, 60℃ storage for 30 days capacity retention rate = C2 / C1*100%.

[0103] 1.4, -20℃ low temperature discharge test: At 25℃, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, then discharge to 2.75V at 0.5C constant current, the discharge capacity is recorded as C3. At 25℃, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, then transfer the battery to -20℃ for 240min, then discharge to 2.75V at 0.5C constant current, the discharge capacity is recorded as C4, -20℃ discharge rate = C4 / C3*100%; wherein, the low temperature discharge capacity retention rate of Examples 1, 2 and Comparative Example 1 is shown in Figure 4 .

[0104] 1.5. Thickness change rate after 30 days storage at 60°C (high temperature storage expansion rate test): Charge the lithium-ion battery at 25°C at a constant current of 1.0C to 4.4V, and charge at a constant voltage of 4.4V to a cut-off current of 0.05C. After the battery is charged, test the battery thickness and record the value as T0. Test the battery thickness after the 30-day storage test at 60°C, and record the value as T1. Battery expansion rate η6 = (T1-T0) / T0*100%; see the high temperature storage battery thickness change rate of Examples 1, 2 and Comparative Example 1. Figure 3 .

[0105] 1.6. Initial DCIR test: Charge the lithium-ion battery at 25°C at a constant current of 1.0C to 4.4V, and charge at a constant voltage of 4.4V to a cut-off current of 0.05C. Then discharge the battery at a constant current of 1.0C for 30 minutes. After standing for 1 hour, discharge it at a constant current of 2.0C for 10 seconds, and calculate the DCIR impedance value of the battery at 50% SOC.

[0106] 1.7. Low temperature DCIR test: Charge the lithium-ion battery at 25°C at a constant current of 1.0C to 4.4V, charge at a constant voltage of 4.4V to a cut-off current of 0.05C, and then discharge the battery at a constant current of 1.0C for 30min. After leaving it for 1h, transfer the battery to -20°C and leave it for 240min. Then discharge it at a constant current of 1.0C for 10s, and calculate the DCIR impedance value of the battery at 50% SOC.

[0107] 1.8. Impedance change rate after 30 days storage at 60°C (high temperature impedance change rate test): Charge the lithium-ion battery to 4.4V at 1.0C constant current at 25°C, charge it to a cut-off current of 0.05C at a constant voltage of 4.4V, then discharge it at a constant current of 1.0C for 30 minutes, leave it for 1 hour, and then discharge it at a constant current of 2.0C for 10 seconds. Calculate the DCIR of the battery at 50% SOC, and record the value as D1. Charge the battery that has completed the 30-day storage test at 60°C at a constant current of 1.0C to 4.4V at 25°C, charge it to a cut-off current of 0.05C at a constant voltage of 4.4V, then discharge it at a constant current of 1.0C for 30 minutes, leave it for 1 hour, and then discharge it at a constant current of 2.0C for 10 seconds. Calculate the DCIR of the battery at 50% SOC, and record the value as D2. Battery impedance change rate = D2 / D1*100%; wherein, the high temperature storage battery impedance change rate of Examples 1, 2 and Comparative Example 1 is shown in Figure 3 .

[0108] 2. The lithium-ion battery prepared in Example 31 was subjected to impedance, cycle and high and low temperature performance tests. The test method was similar to that in Test 1 above, except that the charging voltage was 4.45 V. The test results are shown in Table 2.

[0109] 3. The lithium-ion battery prepared in Example 32 was subjected to impedance, cycle and high and low temperature performance tests. The test method was similar to that in Test 1 above, except that the charging voltage was 4.25 V. The test results are shown in Table 2.

[0110] 4. The lithium-ion battery prepared in Example 33 was subjected to impedance, cycle and high and low temperature performance tests. The test method was similar to that in Test 1 above, except that the charging voltage was 4.2 V. The test results are shown in Table 2.

[0111] Table 2:

[0112]

[0113]

[0114]

[0115] As can be seen from Table 2, compared with the comparative example, the battery of the embodiment shows lower impedance, longer cycle life and better resistance to high / low temperature under high voltage and / or high nickelization conditions;

[0116] Furthermore, by comparing Examples 1-4, it can be seen that the battery of Example 1 has better overall performance, and the batteries of Examples 2 and 4 have better cycle capacity retention rates at 45°C and capacity retention rates after storage at 60°C for 30 days; the battery of Example 3 has smaller thickness change after storage at 60°C for 30 days.

[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a current collector and a positive electrode coating disposed on at least one functional surface of the current collector, wherein the positive electrode coating comprises a positive electrode active material, characterized in that: The chemical composition of the positive electrode active material includes: LiNi x Co y M z O2, wherein M is Mn and / or Al, x+y+z=1, y<0.3; the electrolyte comprises: a first additive and a second additive, the first additive containing at least one of the silicon-based fluorophosphate compounds shown in Formula 1-1 to Formula 1-4: The second additive includes at least one of cyclic sulfate esters, cyclic sulfites and cyclic sulfonate ester compounds.

2. The battery according to claim 1, characterized in that x≥0.8。 3. The battery according to claim 1, characterized in that 0.5≤x≤0.7, And / or, the charging cut-off voltage of the battery is ≥4.3V.

4. The battery according to claim 2, characterized in that The chemical composition of the positive electrode active material includes: LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.83 Co 0.11 Mn 0.06 O2、LiNi 0.92 Co 0.05 Mn 0.03 O2、LiNi 0.8 Co 0.1 Al 0.1 At least one of O2.

5. The battery according to claim 3, characterized in that The chemical composition of the positive electrode active material includes: LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.55 Co 0.15 Mn 0.30 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.65 Co 0.07 Mn 0.28 O2、LiNi 0.6 Co 0.1 Mn 0.3 O2、LiNi 0.55 Co 0.15 Mn 0.30 O2.

6. The battery according to claim 1, characterized in that The cyclic sulfate ester compound includes at least one of vinyl sulfate, propylene sulfate, vinylidene sulfate, catechol sulfate, bis-spiropropylene sulfate, bis-vinyl sulfate, 4,5-bis(4-vinyl sulfate)ethylene carbonate, and methylene methane disulfonate; The cyclic sulfite compounds include ethylene sulfite and / or propylene sulfite; The cyclic sulfonate compound includes at least one of 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, 2,4-butane sultone, 3-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 1-fluoro-1,3-propane sultone, and ethylene sulfonic acid difluoro lithium phosphate triethylamine salt.

7. The battery according to claim 1, characterized in that In the electrolyte, the mass percentage of the first additive is 0.05wt%-5.0wt%; And / or, in the electrolyte, the mass percentage of the second additive is 0.1wt%-4.0wt%.

8. The battery according to claim 7, characterized in that In the electrolyte, the mass percentage of the first additive is 0.5wt%-2.5wt%; And / or, in the electrolyte, the mass percentage of the second additive is 0.5-3wt%.

9. The battery according to any one of claims 7 or 8, characterized in that: In the electrolyte, the mass ratio of the first additive to the second additive is 1:0.1-4.

10. The battery according to any one of claims 1 to 9, characterized in that: It also includes lithium salt and non-aqueous organic solvent; the mass percentage of the lithium salt is 6wt%-25wt%.

Citation Information

Patent Citations

  • Electrolyte additive, electrolyte containing additive and lithium ion battery

    CN112625062A

  • Electrolyte additive for lithium secondary battery, electrolyte for lithium secondary battery comprising same, and lithium secondary battery

    CN114402468A

  • Electrolyte and lithium ion battery

    CN117175008A

  • Electrolyte and battery

    CN117477033A

  • Flame-retardant non-aqueous electrolytic solution and secondary battery using same

    WO2023079988A1